Impact of visual-spatial ability on laparoscopic camera navigation training - Roch, Paul; Brzoska, Julia; Benner, Laura; Kowalewski, Karl-Friedrich; Müller, Philip C.; Kenngott, Hannes Götz; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2018)
BackgroundTechnical limitations of minimally invasive surgery challenge both surgeons and camera assistants. Current research indicates that visual-spatial ability (VSA) has impact on learning of laparoscopic camera navigation (LCN). However, it remains unclear if complexity of LCN tasks influences the impact of VSA. The aim of this study was to examine the influence of VSA on LCN training within tasks of different complexity levels.MethodsThe present study was conducted as a monocentric prospective trial. VSA was assessed with a cube comparison test before participants underwent LCN training. LCN training consisted of three tasks with increasing complexity. Each task was performed four times and performance was assessed each time. Correlations and multivariate regression analysis were used to assess the influence of VSA on LCN skills.ResultsSeventy-one participants were included (35 males). Significant performance improvement and faster completion times were observed from the first to fourth trial of all three LCN training tasks. Significant positive correlations between VSA and performance on LCN task 3 were found (performance: r s = 0.47; p < 0.001, time: r s = −0.43; p < 0.001). Multivariate regression revealed that higher VSA resulted in greater reduction of time between the first trials of LCN training task 3 (B = −1.67, p = 0.031).ConclusionIn the present study, all trainees improved LCN performance during the training. VSA seems to have impact on LCN performance and training progress particularly for complex LCN tasks. The relation of VSA and LCN performance was stronger for less experienced participants and in the beginning of the learning phase.